Science Learning Using e-LKPD Ethno-SiMaYang Tapis Lampung Cloth to Improve Critical Thinking Skills - Loly Suwandani; Sunyono; Viyanti; Dewi Lengkana (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to explain the effect of using the Etno-SiMaYang Lampung Tapis Cloth e-LKPD in improving students' critical thinking skills. This research is R&D research with the Borg and Gall research model stages 1-7. The samples in this study were class VII.1 as the control class and class VII. 2 as the experimental class, the sample was selected using a cluster random sampling technique. The data collection instruments used were teacher and student needs analysis questionnaires, expert validation questionnaires, teacher and student response questionnaires, as well as pretest-posttest questions. The data analysis technique uses the t-test on students' n-Gain values. The research results stated that the expert validation results for construction suitability, content suitability and readability obtained a percentage score of 85.00% which indicated that the e-LKPD product was valid with the criteria "very high". The average percentage of teacher and student responses was 99.00% and 97.10%, which shows that the e-LKPD product is practical with the criteria "very high". The effectiveness of e-LKPD products in improving critical thinking skills in experimental classes can be seen from the average n-Gain for students of 0.71 in the "large" category with the effect size criteria being in the "large" category.